2008
DOI: 10.1074/jbc.m804015200
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Sulfur Cluster N5 Is Coordinated by an HXXXCXXCXXXXXC Motif in the NuoG Subunit of Escherichia coli NADH:Quinone Oxidoreductase (Complex I)

Abstract: , and N6b were misassigned. Here we identified and characterized cluster N5 in the Escherichia coli complex I whose EPR signals had never been detected by any group. Using homologous recombination, we constructed mutant strains of H101A, H101C, H101A/C114A, and cluster N5 knock-out. Although mutant NuoEFG subcomplexes were dissociated from complex I, we successfully recovered these mutant NuoCDEFG subcomplexes by expressing the His-tagged NuoCD subunit, which had a high affinity to NuoG. The W221A mutant was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 44 publications
(21 reference statements)
0
28
0
Order By: Relevance
“…Indeed, similar results were obtained when recombinant aconitase B [4Fe-4S] cluster (Varghese et al, 2003) or phosphogluconate dehydratase [4Fe-4S] cluster (Jang and Imlay, 2007) was expressed in the E. coli copA/cueO/cusA mutant cells grown in LB media supplemented with CuSO 4 (200 μM) (data not shown). We also examined the effect of CuSO4 (200 μM) on native NADH dehydrogenase I which requires multiple iron-sulphur clusters for its catalytic activity (Nakamaru-Ogiso et al, 2008). Using deamino-NADH as specific substrate for NADH dehydrogenase I (Matsushita et al, 1987), we found that addition of CuSO4 (200 μM) dramatically inhibited the enzyme activity of NADH dehydrogenase I but without significantly affecting the activity of pre-existed NADH dehydrogenase I in the E. coli copA/ cueO/cusA mutant cells (Fig.…”
Section: Copper Inhibits the [4fe-4s] Cluster Assembly In The E Colimentioning
confidence: 98%
“…Indeed, similar results were obtained when recombinant aconitase B [4Fe-4S] cluster (Varghese et al, 2003) or phosphogluconate dehydratase [4Fe-4S] cluster (Jang and Imlay, 2007) was expressed in the E. coli copA/cueO/cusA mutant cells grown in LB media supplemented with CuSO 4 (200 μM) (data not shown). We also examined the effect of CuSO4 (200 μM) on native NADH dehydrogenase I which requires multiple iron-sulphur clusters for its catalytic activity (Nakamaru-Ogiso et al, 2008). Using deamino-NADH as specific substrate for NADH dehydrogenase I (Matsushita et al, 1987), we found that addition of CuSO4 (200 μM) dramatically inhibited the enzyme activity of NADH dehydrogenase I but without significantly affecting the activity of pre-existed NADH dehydrogenase I in the E. coli copA/ cueO/cusA mutant cells (Fig.…”
Section: Copper Inhibits the [4fe-4s] Cluster Assembly In The E Colimentioning
confidence: 98%
“…In fact, utilizing P. denitrificans, Thermus thermophilus, Rhodobacter capsulatus and E. coli , several groups succeeded in identifying 8–9 iron-sulfur clusters, N1a, N1b, N2, N3, N4, N5, N6a, N6b, and N7 in each of the peripheral subcomplex arms of complex I (Chevallet et al 1997; Dupuis et al 1998; Flemming et al 2003; Nakamaru-Ogiso et al 2008; Nakamaru-Ogiso et al 2002; Nakamaru-Ogiso et al 2005; Rasmussen et al 2001; Velazquez et al 2005; Yano et al 1999; Yano et al 2003; Yano et al 1994; Yano et al 1995). Those assignments were recently confirmed by demonstration of the X-ray crystal structure of the hydrophilic peripheral part of T. thermophilus complex I that was determined at 3.3 angstrom (Å) resolution (Sazanov and Hinchliffe 2006).…”
Section: The Bacteria Escherichia Colimentioning
confidence: 99%
“…A number of groups have reported spectroscopic parameters ( g -values) and redox properties (midpoint reduction potentials, E mi ) for individual FeS centers [10–14]. The unambiguous assignment of spectra to individual FeS clusters, however, has been difficult due to the similarity of the g -values for certain clusters, the electrostatic interaction between the redox centers, and the relatively similar midpoint reduction potentials (most of the central FeS clusters have long been considered equipotential).…”
Section: Introductionmentioning
confidence: 99%